INDONESIA YANG DIBAYANGKAN: PERISTIWA 1965-1966 DAN KEMUNCULAN EKSIL INDONESIA - Wahyudi Akmaliah (Jurnal Masyarakat dan Budaya, 2015)
As a newly independent country, Sukarno as Indonesian president had a big plan to develop Indonesia, namely to build economic, politic, and governmental infrastructure independently. One way to take was both developing human resource capabilities and creating a new potential generation among Indonesian students by sending them to study in the developed countries. However, the imagined dream had disappeared along with the events of 1965-1966 which marked by the movement of September 30, 1965. This paper focuses on pre and post of the 1965-1966 events by raising two questions; how was Indonesia being imagined by the Sukarno presidency within the context of foreign policy in the Cold War era by sending the Indonesian students for studying overseas? What was the impact of the 1965-966 events that they were facing? This article shows that the event of 1965-1966 does not only break a dream that imagined by Sukarno, but also causes the emergence of Indonesian exiles community that had been finally forced them to become a stateless citizen. Although they are no longer Indonesian citizen, both of their memory and social activities of Indonesia have been still so strong up to now. In the term of Benedict Anderson’s words, they are well-known as community of long-distance nationalism. Kata kunci: Sukarno, the 1965-1966 tragedy, exiles, long distance nationalism